THE SIGNIFICANCE OF EFL TEACHERS MOTIVATIONAL STRATEGIES IN SUPPORTING EVER-CHANGING CLASSROOM LEARNING DYNAMICS - wijaya, kristian florensio (Universitas Muhammadiyah Surakarta, 2024)
Too much concentration and attention has been given to the significant degree of professional development growth without focusing on cultivating more robust educational motivation among globalized EFL educators. To compensate for this previous research drawback, this small-scale library study attempted to profoundly investigate the extent strong motivation strategies can impart extensive support for worldwide EFL educationalists to induce more supportive and positive second language learning climates in the presence of heterogeneous learners. Thus, the researcher thematically analyzed the identical findings generated by 30 previous EFL teachers’ motivational strategies studies. With the employment of a thematic analysis, the researcher could potentially yield more credible, relevant, and contextual research results since conscientious data interpretations were iteratively applied before grouping these particularly generated findings into some similar research theme categories. All these 30 previously published EFL teachers’ motivational strategies studies were adapted from 2017 to 2024 year. The last current 7 years of published studies were the topmost priority to ensure the trustworthiness of all the thematically-subsumed research findings to be in line with the major specific topic forming in this library investigation. The thematically divided research results revealed that robust EFL teachers’ motivational strategies significantly helped second language learners master the desired target language competencies and experience more enjoyable classroom learning climates.